Edge and confinement effects allow in situ measurement of size and thickness of liquid-exfoliated nanosheets - Mc Closkey, David; Nicolosi, Valeria; Duesberg, Georg; Donegan, John; Mc Evoy, Niall; Coleman, Jonathan (My University, 2014)
Two-dimensional nanomaterials such as MoS2 are of great interest both because of their novel physical properties and their applications potential. Liquid exfoliation, an important production method, is limited by our inability to quickly and easily measure nanosheet size, thickness or concentration. Herein, we demonstrate a method to simultaneously determine mean values of these properties from an optical extinction spectrum measured on a liquid dispersion of MoS2 nanosheets. The concentration measurement is based on the size-independence of the low-wavelength scattering coefficient while the size and thickness measurements rely on the effect on edges and quantum confinement on the optical spectra. The resultant controllability of concentration, size and thickness facilitates the preparation of dispersions with pre-determined properties such as high monolayer-content, leading to first measurement of direct-gap MoS2 luminescence in liquid suspensions. These techniques are general and can be applied to a range of 2-dimensional materials including WS2, MoSe2 and WSe2.
PUBLISHED
cited by 1
Keywords: MoS2 nanosheets; MoS2 nanosheets